Human papillomavirus and Chlamydia trachomatis in oral and genital mucosa of women with normal and abnormal cervical cytology - Mosmann, Jessica Paola (2021)
Background: HPV and C.trachomatis are the most prevalent, viral and bacterial STI worldwide. Both commonly have an asymptomatic development and can evolve into a persistent infection which, added to coinfections, may be important cofactors for the oncogenic transformation. Objective: Evaluate the prevalence of oral and genital HPV and C.trachomatis infection in women with normal and abnormal cervical cytology. Study design: The cross-sectional study included 200 swabs, 100 oral and 100 cervical from 50 women with normal and 50 with abnormal cervical cytology. HPV and C.trachomatis infections were detected using PCR with specific primers. Results: HPV DNA was detected in 27% (n = 27/100) of women with normal and abnormal cytology. Out of 100 genital samples we detected HPV DNA in 18% (n = 18/100) and 14% (n = 14/100) out of 100 oral samples. HPV genotypes detected were genotype 6 of low-risk and 16, 31, 52, 58 and 16–31 coinfection of high-risk. C.trachomatis DNA was detected in 49% (n = 49/100) of patients. Out of 100 genital samples we detected C.trachomatis in 35% (n = 35/100) and 31% (n = 31) out of 100 oral samples. There is statistically significant (p < 0.05) between cytology and HPV and C.trachomatis infection but there is no statistically significant between cytology and the other characteristics. Conclusions: Since the histology of oral mucosa resembles that of the uterine cervix, we can anticipate the presence of HPV and other STI which are detected in different lesions of genital areas and the oral mucosa. Therefore, is important C.trachomatis detection and specific treatment in asymptomatic women because this infection may increase the risk of HPV persistence and coinfection induces a pro-inflammatory environment that may promote the carcinogenesis.